Strategies, characteristics, and research gaps for improving microservices coupling design - Gintoro, Gintoro; Sunardi, Sunardi (Institute of Advanced Engineering and Science, 2025)
The popularity of microservices architecture (MSA) has been pushed by the demand for scalable, maintainable, and efficient applications in the fastchanging digital ecosystem. The objective of this study is to determine strategies for improving service coupling in MSA, analyze the circumstances in which these strategies are successful, and recommend areas of research that need further development for future enhancements. We employed a systematic literature review (SLR) and the seven research gap methodology developed by Müller-Bloch and Kranz to pinpoint 10 essential strategies, such as API gateway and domain-driven design (DDD). The results of our study indicate that the effectiveness of each technique is contingent upon specific design criteria for the microservices, such as the presence of separate read and write operations for command query responsibility segregation (CQRS). To further enhance these techniques, it is crucial to address the research gaps that have been highlighted, particularly the lack of empirical studies on long-term repercussions. This study offers theoretical insights and practical assistance on how to improve the connection between services, thereby enabling the development of more resilient and easily maintainable applications based on MSA.